Correction: Atomic layer deposition of Cu(i) oxide films using Cu(ii) bis(dimethylamino-2-propoxide) and water. Issue 18 (28th April 2017) - Avila, J. R.; Peters, A. W.; Li, Zhanyong; Ortuño, M. A.; Martinson, A. B. F.; Cramer, C. J.; Hupp, J. T.; Farha, O. K.
Abstract : Correction for 'Atomic layer deposition of Cu(i ) oxide films using Cu(ii ) bis(dimethylamino-2-propoxide) and water' by J. R. Avila, et al., Dalton Trans., 2017, DOI: ; Web:10.1039/c6dt02572b .